Aplication of infra-red thermometry to irrigation of bean: growth and yield - Pazzetti, Gustavo Adolfo; Oliva, Marco Antonio; Lopes, Nei Fernandes (Pesquisa Agropecuaria Brasileira, 1993)
Field grown bean (Phaseolus vulgaris L.) plants were subject to four irrigation regimes to establish the relationship between canopy temperature and yield, in an attempt to use infra-red thermometry for monitoring to need of irrigation. The effects of different irrigation regimes were evaluated using dry matter production, variations in leaf area, rate of dry matter accumulation, variation of yield components, and productivity. Lower values in growth parameters corresponded to plants grown under lower frequency of irrigation which also corresponded to higher canopy temperatures. Decreased in yield components were also higher in plants that suf-fered stress. The results indicated that the canopy temperature showed closely relationship with yield components and with productivity and also with stress evolution which makes possible the best use of infra-red thermometry for the monitoring of irrigation.
Keywords: Phaseolus vulgaris; monitoring temperature variations; irrigation monitoring; dry matter; canopy temperature; leaf area